Figur Kyai dan Pendidikan Karakter di Pondok Pesantren - Masrur, Mohammad (Universitas Islam Negeri (UIN) Jurai Siwo Lampung, 2017)
Pesantren is an important institution in Indonesia to build generation character. Dormitory system (Mondok) has its own advantages in the process of transformation of science intensive theology. Kyai figure was in control in the process of learning activities for Islam in these institutions is the key to the success of a boarding school. Model Kyai's leadership is leadership Charismatic with a spirit of exemplary, where figure Kyai seen by the public as a person who is an expert in the field of religion, seen as able to provide solutions in the areas of social and religious, are also able to contribute to the nation in building younger generation is characterized as widened national educational purposes. Character education is what an Kyai include sincerity education, independence education, brotherhood education and discipline educatio. All of these character-building process carried out on the basis of exemplary. That is all that is taught by a Kyai are sciences that have been exemplified in advance. With exemplary zeal in educating the students, then we may see every graduate boarding school has a character similar to them Kyai.